1980
DOI: 10.1017/s0007485300007781
|View full text |Cite
|
Sign up to set email alerts
|

On the biting activities of some anthropophilic Amazonian Simuliidae (Diptera)

Abstract: Quantitative observations on the biting activities of Simulium simplicicolor Lutz and 5. sanguineum Knab s.l. at Aripuana, Mato Grosso, Brazil, and S. guianense Wise and S. sanguineum s.l. at Urua, Pari, were made during the wet and dry seasons between June 1978 and August 1979. The species demonstrated characteristic attacking patterns regardless of abundance or environmental conditions. S. simplicicolor, S. guianense and S. sanguineum s.l. at Urua demonstrated bimodal biting patterns with early morning and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
8
0
2
Order By: Relevance
“…Andreazze et al (2002) observed minor activity of P. incrustata in temperatures averaging lower than 20°C and greater between 23.24 and 26.53°C. Lacey & Charlwood (1980) verified that the S. sanguineum (= Cerqueirellum sp.) activity was limited in the beginning of the morning when the temperature was lower than 18°C.…”
Section: The Influence Of Climatic Parameters In the Haematophagic Damentioning
confidence: 89%
See 1 more Smart Citation
“…Andreazze et al (2002) observed minor activity of P. incrustata in temperatures averaging lower than 20°C and greater between 23.24 and 26.53°C. Lacey & Charlwood (1980) verified that the S. sanguineum (= Cerqueirellum sp.) activity was limited in the beginning of the morning when the temperature was lower than 18°C.…”
Section: The Influence Of Climatic Parameters In the Haematophagic Damentioning
confidence: 89%
“…According to Lacey & Charlwood (1980), some factors act as a block, creating favorable terms for the bite stimulus in the morning or evening period. Simuliids initiate their activity in the first hours of the morning, stimulated by luminosity (Peterson & Wolfe, 1956).…”
Section: Introductionmentioning
confidence: 99%
“…But, in almost one century, only one study was carried out on the anthropophilylic habits of the species (LACEY & CHARLWOOD 1980), In spite of the fact that it considered anthropophilic, and is present in a region next to the Amazonian focus of onchocerciasis (SHELLEY et al 1997), and given the possibility of expansion of the disease (SHELLEY et al 2000), very little is known about the biology of this species (PY-DANIEL 1982). …”
Section: 15 16mentioning
confidence: 99%
“…Os trabalhos relacionados aos Simulídeos iniciados por Cerqueira ainda estão no estágio de estudos descritivos e zoogeográficos (Gorayeb & Pinger, 1978), com um único estudo biológico visando possíveis métodos de controle biológico, desde os potenciais vetores da Mansonella ozzardi e Onchocerca volvulus (Mello, ef a/., 1973;Mello & Silva, 1974;PyDaniel, 1979;Lacey & Charlwood, 1980;Py-Daniel & Shelley. 1980).…”
Section: Estudos Relacionados Aos Vetores Dos Parasitasunclassified